Lanny : a Novel - Porter, Max (Minneapolis, MN : Graywolf Press, 2019)
"Not far from London, there is a village. This village belongs to the people who live in it and to those who lived in it hundreds of years ago. It belongs to England's mysterious past and its confounding present. It belongs to Mad Pete, the grizzled artist. To ancient Peggy, gossiping at her gate. To families dead for generations, and to those who have only recently moved here. But it also belongs to Dead Papa Toothwort who has woken from his slumber in the woods. Dead Papa Toothwort, who is listening to them all. Chimerical, audacious, strange and wonderful - a song to difference and imagination, to friendship, youth and love, Lanny is the globally anticipated new novel from Max Porter."--Publisher's description.
Keywords: Villages -- Fiction; Time travel -- Fiction; England -- Fiction; Paranormal fiction